Fabrication and physicochemical characterization of g-C3N4/ZnO composite with enhanced photocatalytic activity under visible light - Mathialagan, Abinaya (Elsevier, 2020)
The present study deals with the synthesis, characterization and photocatalytic activity of g-C3N4/ZnO composite towards the degradation of significant dyes like Malachite green (MG), Rhodamine-B (Rh-B), Congo red (Con-R), and Red ink (RI) solution. For the synthesis of the g-C3N4/ZnO composite, we have adopted the chemical precipitation method where the composite was thoroughly analyzed for the crystallinity, optical performance, and morphology by making use of the instrumental methods like powdered X-ray diffraction (PXRD), Fourier transform-infrared spectroscopy (FTIR), UV-Vis diffuse reflection spectroscopy (UV-Vis), Transmission electron microscopy (TEM), Atomic force microscopy (AFM), and thermogravimetric (TGA) analysis. It was found from the PXRD and TEM analysis that the composite maintains hexagonal wurtzite phases for the ZnO and g-C3N4 compounds, while the UV-Vis spectrum confirmed that the composite's absorption edge is getting shifted to the lower energy and wavelength region as compared to ZnO. On testing the photocatalytic activity under the UV light towards the dye degradation, the g-C3N4/ZnO composite is indicated to have significant performance and thereby supporting the synergistic impact of each component. The observation of such activity in the g-C3N4/ZnO composite can be investigated to be due to the composite's enhanced stability in the aqueous solution (supported by the lower amounts of Zn2+), in addition to the improved electron-hole separations and synergistic photocatalytic mechanism between ZnO and g-C3N4.